Interrupting Listening to Children: Researching with Children's Secret Places in Early Childhood Settings. Issue 2 (June 2014) - Moore, Deborah
THIS PAPER EXAMINES A definitive turning point in an early childhood research study involving children's construction of secret places juxtaposed against the challenge of authentically researching with children. The study was a qualitative case study theoretically positioned within the sociology of childhood. It used child-based research methods and participatory tools from the Mosaic Approach. A dramatic shift in the study occurred when the author realised that to move beyond the dominant discourse of past paradigms required an interruption to the methodological approach of adult-contrived interviews to an approach of listening to but not fully knowing children.